A taxonomic study of Dinapsis Waterson, 1922 from Madagascar (Hymenoptera: Megalyridae, Dinapsini): crested wasps of the hirtipes species-group - Mita, Toshiharu; Shaw, Scott Richard (Zootaxa, 2020)
Five new species, Dinapsis albicauda, n. sp., D. cresta, n. sp., D. luteus, n. sp., D. planifrons, n. sp., and D. scriptus, n. sp. are described from the island of Madagascar. The Dinapsis hirtipes species-group is proposed based on D. hirtipes Hedqvist, 1967 and the five newly described species. A key to species of the D. hirtipes species-group is provided.